ANALISIS KEEFISIENAN USAHATANI JAHE (Studi Kasus di Kecamatan Ampel, Boyolali) EFFICIENCY ANALYSIS OF GINGER FARMING (Case Study in Ampel District, Boyolali) - , Waridin (Pembangunan Pedesaan, 2007)
The objective of the study was to analyse the technical, price, and economic efficiency of ginger farming. This study was also intended to analyse the revenue and costs of the farming. Results of the study indicated that the production factors of land, labour, seeds, and organic fertilizer influenced significantly to the ginger production. The average technical, price, and economic efficiency reached 0.9252, 3.9618, and 3.6655, respectively. The coefficients of more than 1 implied that the ginger farming was not efficient yet and still possible to increase additional inputs. With the revenue-costs ratio of 1.82, the ginger farming was still profitable.